Profitability and Liquidity as Key Drivers of Firm Value: The Moderating Role of Corporate Social Responsibility - Ramadhan, Hasan Mubarok; Simatupang, Frido Saritua (Universitas Kuningan, 2025)
There has been tremendous growth in the disclosure of sustainability reports, and it is now an essential component for all organizations. Using the SRI-KEHATI stock index on the Indonesia Stock Exchange as a case study, this research intends to uncover and compile data pertaining to the impact of sustainability report disclosure on firm value, as mediated by Corporate Social Responsibility (CSR), through the effects of Return On Asset (ROA) and Current Ratio (CR) from 2020 to 2023. A total of 36 firms make up the study's population, and 9 of those companies are selected at random throughout the course of 4 years. Using a quantitative approach, this study makes use of descriptive and associative research methodologies. This research used purposive sample approaches in conjunction with non-probability methods. The website of the Indonesia Stock Exchange (IDX) served as the data source for this research. For the years 2020–2023, the information is sourced from SRI-KEHATI index sustainability reports as well as yearly financial reports. Firm value is positively affected by Return On Asset (ROA), according to this study's findings. The worth of the company is unaffected by the current ratio (CR). The current ratio (CR) and return on assets (ROA) both influence the value of a company at the same time. There is no moderating effect of corporate social responsibility (CSR) on the correlation between ROA and company value. Current Ratio (CR) and company value are unmodified by corporate social responsibility (CSR).